The Responsibilities of Notaries/Land Deed Making Officials (PPAT) to Electronic Mortgages Based on the Regulation of the Minister of Agrarian - Mega Arum Saputri; Gunarto Gunarto; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Notary is a public official who is authorized to make authentic deeds as long as the making of certain authentic deeds is not specific to other public officials. Notary, in this case, is a public official who is given the authority to make authentic deeds regarding certain legal actions regarding land rights or property rights over apartment units, while PPAT deeds are deeds made by PPAT as evidence that certain legal actions have been carried out regarding land rights or ownership rights over flat units, PPAT deed is a tool to prove that a legal act has been committed. The problems in this thesis are: (1) What is the responsibility of a PPAT Notary for electronic mortgage certificates based on the Minister of Agrarian Regulation Number 9 of 2019 ?, (2) What are PPAT Notary Obstacles in storing electronic mortgage documents? The Land Office regarding electronic mortgage certificates based on the Minister of Agrarian Regulation Number 9 of 2019? The method used is juridical empirical, with descriptive analytical specifications of data collected with primary data from field research and secondary data from literature studies, while qualitative data. The results of this study are: (1) The responsibility of the Notary/PPAT for electronic mortgage documents based on the Minister of Agrarian Regulation Number 9 of 2019 is to assist the government's duties. HT-el service is a form of service provision from the Ministry of ATR/BPN in facilitating services to the community by taking advantage of developments in information technology. PPAT is exempted from the obligation to represent the applicant (creditor) but PPAT is still obliged to submit the deed it has made, including APHT as quickly as possible and no later than 7 days. (2) Obstacles to the Notary/PPAT in storing electronic mortgage documents include a) constraints from the Creditor (Bank), where in each Notary-PPAT credit binding process b) Constraints from the Debtor (Client). c) Constraints from BPN, which is for clients who want all the management processes such as checking, registration, roya and so on related to the installation of Mortgage Rights at the BPN office can use an accelerated process even though they have to pay more than the specified administrative fee. (3) Efforts by the Notary/PPAT and the Land Office to electronic mortgage certificates based on the Regulation of the Minister of Agrarian Affairs Number 9 of 2019 are that PPAT Notaries need to apply the principle of prudence in examining HT-el certificates submitted by the tappers. The suggestion in this research is that the Notary Public/PPAT needs to make readiness in the procurement of electronics and technology that is qualified in HT-el registration and needs to apply the principle of prudence.